Ways to improve the organization of physical education students in higher education - Futornyі S.M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Purpose . Carry out an analysis of the conceptual approaches to improve the organization of physical education students. Material and methods . An expert survey of physical education teachers of higher educational institutions are not athletic profile. Results . Been a significant interest in the issues raised, the interest of teachers and students in finding solutions to these pressing problems, the desire to be an active participant in the development of educational policy health formative. Found that the main ways of improving the physical education of youth in the education system should be the formation of the need for health promotion by means of physical culture and sports. And - improving the quality of the educational process and ensure its highly qualified staff, modern scientific - methodical complexes relevant material - technical equipment. Conclusions . Revealed a coherent picture vision problems and prospects of improvement of physical education students. This gives you the opportunity to structure their priority problems and to develop solutions for the purpose of successful implementation of health- education strategy.